Mode-matching metasurfaces: coherent reconstruction and multiplexing of surface waves - Lin, Jiao (2015)
Metasurfaces are promising two-dimensional metamaterials that are engineered to provide unique properties or functionalities absent in naturally occurring homogeneous surfaces. Here, we report a type of metasurface for tailored reconstruction of surface plasmon waves from light. The design is based on an array of slit antennas arranged in a way that it matches the complex field distribution of the desired surface plasmon wave. The approach is generic so that one can readily create more intricate designs that selectively generate different surface plasmon waves through simple variation of the wavelength or the polarization state of incident light. The ultra-thin metasurface demonstrated in this paper provides a versatile interface between the conventional free-space optics and a two-dimensional platform such as surface plasmonics.